Ranma 1/2. Vol. 35 - Takahashi, Rumiko, 1957- (Ranma 1/2, 2006)
Ranma rescues the daughter of the guide to the infamous cursed springs from a flock of evil birdmen. She tells Ranma that the map of the springs must be protected from the bird-men or the springs will dry up. When the bird fiends take Shampoo, Ranma and friends are thrust into battle.